Antistress potential of acetone extract of Zingiber officinale Roscoe on biochemical and oxidative stress parameters in Labeo calbasu (Hamilton 1822) fingerlings subjected to acid stress - Chanu, Thongam Ibemcha; Dam Roy, S.; Sharma, Arun; Biswas, Pradyut; Siddhya, G. M.; Das, Arabinda (Indian Journal of Fisheries, 2013)
A 30 days feeding trial was conducted to study the antistress property of acetone extract of Zingiber officinale against acid stress in Labeo calbasu fingerlings. Fish fingerlings (7.34 Â± 0.06 g; average weight Â± S e ) were randomly distributed into 4 treatment groups, each with 3 replicates and were fed with four diets containing different levels of Z. officinale acetone extract (0, 0.05, 0.5 or 5%). The potential antistress ability of Z. officinale acetone extract was assessed in terms of production of serum cortisol, serum glucose, serum cholesterol, serum triglycerides, triiodothyronine (T 3 ), thyroxine (T4), alanine amino transferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (ALP), catalase (CAT), superoxide dismutase (S o D) and glutathione S transferase (GST) while they are exposed to acidic water with pH 5.5 for 24 h. Acid stress significantly increased serum cortisol, glucose, cholesterol, T3, T4, ALT, AST and ALP levels and decreased the triglycerides level in all the treatments. Z. officinale acetone extract in fish diet at a minimum level of 0.5% concomitantly, reduced the stress in L. calbasu fingerlings.